Contrast Enhanced Ultrasonography and Carotid Plaque Imaging: from the Hemodynamic Evaluation to the Detection of Neoangiogenesis - The New Approach to the Identification of the Unstable Plaque: from Morphology to Patophysiology - Giannoni, Maria Fabrizia; Vicenzini, Edoardo; Monaco, Claudia; Cao, Piergiorgio (IntechOpen, 2011)
None